Os Pequenos aqüíferos aluviais nas áreas cristalinas semi-áridas: funcionamento e estratégias de gestão. Estudo de caso no nordeste brasileiro - Burte, Julien Daniel Pierre (2008)
In semi-arid crystalline areas, small alluvial aquifers are important hydrological resources for rural populations but limited, whose dynamics are strongly influenced by human activities. The sustainability of the availability of these resources depends on the development of management strategies adapted to the physical environment, but also to local socioeconomic characteristics. A river basin located in the crystalline area of ​​the semi-arid Northeast, where the use of small aquifers Alluvial developed rapidly in the last decade, a study was carried according to a two-pronged approach 1) physical, to characterize these water resources traditionally understudied and propose a model of its hidrossalino operation, and 2) to characterize socioeconomic user groups and local strategies to use and management of water resources. This study is based on six years of data (monitoring and characterization studies of the physical and socio-economic means) and construction of models of water balances and mass salts to the monthly time step that allowed the quantification of the main terms of the balance of the aquifer alluvial and discussion of interactions with other water resources (crystalline aquifer, weirs). The chances of hydrological functioning were tested with a spatialized model of physical basis. Scenarios for the evolution of the exploitation of water resources were built from the major internal factors (physical and anthropogenic) and external (public policy) that determine its dynamics and its management. The impact of these scenarios on water availability (in terms of quantity and quality) was simulated in the short and long term, which allowed to show the importance of an upstream integrated management / downstream water resources. Finally, a regional mapping method of small alluvial aquifer is developed, allowing the evaluation of the annual volume of potentially exploitable water in a large basin.